Notes on feeding and mating behavior of Anolis biporcatus (Squamata: Dactyloidae) in Costa Rica - Chaves Acuña, Wagner Josue (2024)
Anoles are small to midsize tree-dwelling lizards that inhabit a broad range of microhabitatsalong the vertical strata of Neotropical forests, ranging from those that are highly terrestrial orthat occupy lower levels of the forest canopy to species that thrive in higher levels within thecanopy. Natural history information, particularly for species that live at canopy levels like Anolisbiporcatus remains scarce. This diurnal lizard can reach a total length of approximately 70–107 mm and ranges from southern Mexico to western Ecuador at elevations from near sea level to about 1220 m. a.s.l. Individuals are typically green but can exhibit significant color changes. Males have dewlaps with a blue center and a white base bordered by a red margin, while females possess white dewlaps without the distinctive coloration seen in males. Anolis biporcatus lays a few eggs in mosscovered branches and tends to be active during the rainy season. It also perches on trunks at heights between 20 cm to 18 m and consumes small to mid-size arthropods such as beetles, ants, and spiders. Individuals are keratophagous and consume small lizards as vertebrate prey. Due to its arboreal behavior, information about its diet and reproductive biology remain limited becauseindividuals seldom descend from the canopy. To better understand the natural history of this species, we present a series of field observations on adults of A. biporcatus at Veragua Rainforest in Las Brisas de Veragua, Limón Province, Costa Rica.